Relationship Between Workplace Spirituality And Employee Engagement In The Milling Sector Of Pt. Family Raya - Ria Okfrima; Budi Harto; M. Asbullah; Nila Pratiwi; Marina Lestari Pasaribu (Institute of Computer Science (IOCS), 2022)
This study aims to see the relationship between Workplace Spirituality and Employee Engagement in the Milling Sector of PT. Famili Raya Padang. The independent variable in this study is Workplace Spirituality and the dependent variable is Employee Engagement. The measuring tools used in this study are the Workplace Spirituality scale and the Employee Engagement scale. The sampling technique used in this study was a saturated sample technique with a total sample of 38 people. Test the validity and reliability using the Cronbach Alpha technique. The results of the validity coefficient on the Workplace Spirituality scale range from 0.361 to 0.852, while the reliability coefficient is 0.944. The results of the validity coefficient on the Employee Engagement scale range from 0.620 to 0.874, while the reliability coefficient is 0.978. The results of data analysis showed the magnitude of the correlation coefficient was 0.507 with a significant level of p = 0.001. This means that there is a significant relationship with a positive direction between Workplace Spirituality and Employee Engagement in the Milling Sector of PT. Family Raya Padang.